(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nowadays, due to the widespread use of mobile phones and the proliferation of mobile towers the human body parts especially the heart are getting affected. Furthermore, these waves are ubiquitous in our modern society, with various sources emitting these waves in our environment. As medical devices become more prevalent and wireless technologies continue to advance, concerns have been raised regarding the potential impact of electromagnetic waves on human health. It is important to monitor the condition of your heart. With the increase in the number of mobile phones, there is also an increase in electromagnetic radiation, which can affect the human heart. The heart is an important component of the human body and an electrocardiogram (ECG) can provide valuable information about its condition. ECG parameters can show how well the heart is working. In this paper, the author proposes how ECG parameters change under the influence of mobile phones in three different situations. A comprehensive experimental setup was devised. A group of healthy human subjects volunteered to participate in the study, with each subject undergoing ECG recording under controlled conditions. The subjects were exposed to varying intensities and frequencies of electromagnetic waves generated by a standardized source. Statistical analysis was performed to compare the ECG measurements obtained during exposure to electromagnetic waves with those obtained in a controlled environment without electromagnetic wave exposure. This study contributes to the growing body of research on the potential health effects of electromagnetic waves. By specifically focusing on the ECG signal, which is vital for cardiovascular diagnostics, this research provides valuable insights into the safety and reliability of using ECG in environments with electromagnetic wave exposure.